Sustainable E-Commerce through Data Insights: Semantic Analysis of Customer Preferences for SDG aligned Business Practices - Elsie, Elsie; Tusiadi, Herman; Kristian, Joshua (PT FORMOSA CENDEKIA GLOBAL, 2025)
Aligning e-commerce with Sustainable Development Goals (SDGs) requires understanding vast customer data. This study uses semantic analysis to analyze customer preferences, focusing on aligning business strategies with SDG 8 (economic growth) and SDG 12 (responsible consumption). This research is distinct by empirically bridging unstructured customer reviews and actionable SDG-aligned practices, moving beyond traditional sentiment analysis. Using a big data approach, the study employs PySpark and logistic regression to evaluate customer reviews via parsing, preprocessing, and model training. Findings reveal product quality, convenience, and pricing significantly influence satisfaction. These insights help businesses reduce waste (SDG 12) and optimize workflows (SDG 9). By aligning data insights with SDGs, businesses can promote sustainable consumption and economic growth.